Zasady i tryb udzielania dotacji celowych dla gmin i powiatów na budowę i remonty dróg lokalnych w ramach programów wieloletnich - Ofiarska, Małgorzata (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2019)
Specific-purpose grants from the state budget granted under long-term programmes for construction and modernisation of local roads are an important funding source for the execution of own tasks of communes and districts. The present study has demonstrated that application of the legal form of specific-purpose grant allows for a close connection of the granted funds to the execution of a specified public task – reconstruction, construction, or renovation of communal and district roads. The granting entity exercises control in terms of the purpose and timeframe of grant utilisation, whereas the receiving entity is held liable in case of improper disbursement or settlement of the grant. Long-term programmes oriented towards funding such tasks, implemented since 2008, have become an important support instrument for local initiatives aiming at entrepreneurship development and increasing the attractiveness of communes and districts as investment locations for both local and nonlocal entrepreneurs. Both the procedure adopted for accepting applications for specific-purpose grants and the use of grant contracts facilitate the maintenance of proper donor-beneficiary relationships. The socioeconomic effects of these long-term programmes involve a considerable improvement of the technical condition of local road infrastructure, which previously represented a significant developmental barrier for many regions of Poland.
Keywords: specific-purpose grants; local roads